Collaboration of Parents and Teachers in Supporting the Success of Inclusive Education in Senior High Schools - Zuhri, Zuhri; Afriani, Gusma (Civiliza Publishing, Indonesia., 2025)
Inclusive education at the senior high school level presents complex challenges that require active collaboration between parents and teachers to ensure the academic success and social development of students with special educational needs (SEN). However, in the Indonesian context, such collaboration is often limited due to socio-cultural barriers, lack of parental understanding, and insufficient institutional support. This study aims to explore how parent-teacher collaboration is implemented, the obstacles encountered, and its impact on inclusive education practices in senior high schools. Using a qualitative descriptive approach, the research was conducted over three months in two inclusive senior high schools in Indonesia through semi-structured interviews, observations, and document analysis. The findings reveal that while both parents and teachers recognize the importance of collaboration, its realization remains inconsistent, influenced by socio-economic disparities, lack of structured communication platforms, and varying levels of awareness about inclusive education. The study also highlights the role of school leadership and emotional connections in fostering effective partnerships. It concludes that improving collaboration requires institutional commitment, parental empowerment, and teacher capacity-building.